2013
DOI: 10.1007/s10461-013-0602-1
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Alcohol Use Among Individuals with HIV: Relations with Everyday Memory Functioning and HIV Symptom Severity

Abstract: Problematic alcohol use has been shown to negatively impact cognitive functions germane to achieving optimal HIV health outcomes. The present study, a secondary data analysis, examined the impact of problematic alcohol use on aspects of everyday memory functioning in a sample of 172 HIV-infected individuals (22 % female; M age = 48.37 years, SD = 8.64; 39 % Black/nonHispanic). Additionally, we tested whether self-reported memory functioning explained the relation between problematic alcohol use and HIV symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 103 publications
(145 reference statements)
1
7
0
Order By: Relevance
“…Therapeutic advances for HIV infection have greatly improved mortality rates among those living with HIV, subsequently generating a more chronic disease state [11-14]. Various co-morbidities, including alcohol abuse, are now important concerns for the effective management of patient health [15-17]. Because chronic alcohol abuse can alter immunological and metabolic pathways that also affect disease progression among HIV-infected patients, several studies have sought to evaluate how alcohol use impacts HIV disease measures [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic advances for HIV infection have greatly improved mortality rates among those living with HIV, subsequently generating a more chronic disease state [11-14]. Various co-morbidities, including alcohol abuse, are now important concerns for the effective management of patient health [15-17]. Because chronic alcohol abuse can alter immunological and metabolic pathways that also affect disease progression among HIV-infected patients, several studies have sought to evaluate how alcohol use impacts HIV disease measures [18]).…”
Section: Introductionmentioning
confidence: 99%
“…HD is also associated with risky behaviors, low treatment adherence, and rapid progression to AIDS (Armstrong et al., ). HD pattern of alcohol consumption has obvious consequences in the immune system (Pandrea et al., ), liver (Gitto et al., ; Ioannou et al., ), and brain cells (Gitto et al., ; Heinz et al., ). Alcohol use disorder was associated with advanced hepatic fibrosis among HIV‐1‐monoinfected patients (not influenced by hepatitis B and C coinfection) in a previous cross‐sectional study (Kim et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to HIV, combined with alcohol or substance use, may have a significant negative impact on cognition in this target population. Heinz et al showed that excessive alcohol use was directly associated with lower total memory functioning, poorer retrieval abilities, and greater HIV symptom severity due to noncompliance with antiretroviral therapy (ART) [97]. However, patients in their 50s and older were more likely to adhere to ART when drinking [98].…”
Section: Other Factorsmentioning
confidence: 99%